Avaliação da sustentabilidade de agroecossistemas dos agricultores participantes da feira do produtor em Pato Branco - PR: uma abordagem ao longo do tempo - Lora, Mayza Izadora (2019)
Within general parameters who support the sustainability it is noticed that exist many dimen sions who need of special attent ion as your subsistence and it’s become emerging, specially inside of economical dimensions, social and environmental. When approaching of farmers realit y, you see the social sustainability of then becomes ever more weskened and for that, should be looked for new methodologies and strategies, that can conduct a survey more minute of principal critical points existing and still and from these look for indic ators who can serve like forces and opportunities, solving the threats and weakeness presented to the balance of agroecossistems sustainability. Face of it, this researching had as principal objective evaluate the sustainability of carnies agroecossistems from Pato Branco PR municipality over the time, for that was made an analysis based in the MESMIS methodology which grew over the time, allowing to be held many stages of the same research from a kit of sustainability indicators. When conduct na analysis based in the time 1 of research, in 2015 year it was noticide the necessity to add two others methodologies for to support the lifthing and characterisation of indicators, the social network analysis ARS and the analysis SWOT Strengths, Weaknesses, Op portunities and Threats) Threats). Like this, in this second moment of this research, was selected and analysed 112 indicators, distribuited between the dimensions social, environmental and economical. After the analysis of agroecossistems showed good levels of sus tainability, however, some points concerning to the social and environmental dimension still are frayed needing more attention, like the efficiency of work hand, laisure, education, conditions of water resourses, uses of greenhouses, cares durin g the agroc hemical applications . Already the economical dimension found well strengthened. It is suggested set strategies to the formation of a social network involving all the carnies farmers for they can search support of institutions who aid the resolution of the critical points in an united and effective way. It is done necessary that is leaning and strengthened na association of these carnies, and that this acts on behalf of the very common, strengthened consequently the agroecossistems sustainability in all the your dimensions.